The Protective Effect of Fucoidan in Rats with Streptozotocin-Induced Diabetic Nephropathy - Jing Wang; Huaide Liu; Ning Li; Quanbin Zhang; Hong Zhang (Marine Drugs, 2014)
Diabetic nephropathy (DN) has long been recognized as the leading cause of end-stage renal disease, but the efficacy of available strategies for the prevention of DN remains poor. The aim of this study was to investigate the possible beneficial effects of fucoidan (FPS) in streptozotocin (STZ)-induced diabetes in rats. Wistar rats were made diabetic by injection of STZ after removal of the right kidney. FPS was administered to these diabetic rats for 10 weeks. Body weight, physical activity, renal function, and renal morphometry were measured after 10 weeks of treatment. In the FPS-treated group, the levels of blood glucose, BUN, Ccr and Ucr decreased significantly, and microalbumin, serum insulin and the β2-MG content increased significantly. Moreover, the FPS-treated group showed improvements in renal morphometry. In summary, FPS can ameliorate the metabolic abnormalities of diabetic rats and delay the progression of diabetic renal complications.